Optimisation of composite bone plates for ulnar transverse fractures. (April 2016) - Chakladar, N.D.; Harper, L.T.; Parsons, A.J.
Abstract: Metallic bone plates are commonly used for arm bone fractures where conservative treatment (casts) cannot provide adequate support and compression at the fracture site. These plates, made of stainless steel or titanium alloys, tend to shield stress transfer at the fracture site and delay the bone healing rate. This study investigates the feasibility of adopting advanced composite materials to overcome stress shielding effects by optimising the geometry and mechanical properties of the plate to match more closely to the bone. An ulnar transverse fracture is characterised and finite element techniques are employed to investigate the feasibility of a composite-plated fractured bone construct over a stainless steel equivalent. Numerical models of intact and fractured bones are analysed and the mechanical behaviour is found to agree with experimental data. The mechanical properties are tailored to produce an optimised composite plate, offering a 25% reduction in length and a 70% reduction in mass. The optimised design may help to reduce stress shielding and increase bone healing rates. Graphical abstract: Highlights: Composites are found to be potential candidates for future bone implant materials. 25% shorter and 70% lighter composite plates are proposed, in comparison to metals. A fractured ulnar model is created which agrees well with experimental data. Screw positions significantly affect the construct stiffness upto a factor of 2.